Are EFL Writers Motivated or Demotivated by Model Texts and Task Repetition? Evidence from Young Collaborative Writers - Lázaro-Ibarrola, Amparo; Villarreal, Izaskun (International Journal of English Studies, 2021)
Studies on multi-stage writing tasks with adults and children have shown that model texts and task repetition aid language acquisition, especially when learners work in collaboration. However, these studies have not included measures of task motivation, which is vital in young learners (YLs) and could help develop a more comprehensive understanding of task effectiveness. The present study analyses task motivation in 24 EFL YLs writing in pairs during three sessions divided into a model group (MG) and a task repetition group (TRG). Results show that students’ task motivation is high in general but declines in the MG while it is maintained in the TRG. As for the motives, working together is the main reason students give to justify their positive scores. These results complete previous knowledge about models and TR, reinforce the value of collaborative writing and encourage the inclusion of motivation measures in task-based research.